Anaerobic Conversion of Proteinogenic Amino Acids When Methanogenesis Is Inhibited: Carboxylic Acid Production from Single Amino Acids - Leandro Conrado; Jacob McCoy; Leo Rabinovich; Mona Davoudimehr; Panagiota Stamatopoulou; Matthew Scarborough (Fermentation, 2024)
Proteins are an abundant biopolymer in organic waste feedstocks for biorefining. When degraded, amino acids are released, but their fate in non-methanogenic microbiomes is not well understood. The ability of a microbiome obtained from an anaerobic digester to produce volatile fatty acids from the twenty proteinogenic amino acids was tested using batch experiments. Batch tests were conducted using an initial concentration of each amino acid of 9000 mg COD L−1 along with 9000 mg COD L−1 acetate. Butyrate production was observed from lysine, glutamate, and serine fermentation. Lesser amounts of propionate, iso-butyrate, and iso-valerate were also observed from individual amino acids. Based on 16S rRNA gene amplicon sequencing, Anaerostignum, Intestimonas, Aminipila, and Oscillibacter all likely play a role in the conversion of amino acids to butyrate. The specific roles of other abundant taxa, including Coprothermobacter, Fervidobacterium, Desulfovibrio, and Wolinella, remain unknown, but these genera should be studied for their role in fermentation of amino acids and proteins to VFAs.